An Investigation of Presumptive Synergism of Oil Palm Bunch Ash and Sawdust Amendments in Remediation of crude oil Spiked Soil - Ejikeme Albert; Di Anyanwu (Journal of Applied Sciences and Environmental Management)
Presumed synergistic effect of combined amendment of crude oil spiked soil with oil palm bunch ash and sawdust was carried out in a laboratory experiment. Two kilogram (2 kg) of sandy soil was placed in each of five plastic vessels labeled TA, TB, TC, TD and TE. TA was left in its natural state while the others were each polluted with 6.7% v/w of crude oil. TB was not given any remediation amendment. TC and TD were each amended with 13.3% of oil palm bunch ash and sawdust respectively while TE was amended with 13.3% each of oil palm bunch ash and sawdust. The setups were replicated five times and watered twice weekly. Results showed that soil pH increased from 8.7±0.04 to 10.5±0.06, 5.3±0.01 to 8.5±0.04 and 5.6±0.18 to 11.5±0.15 for TC, TD and TE respectively. Percentage total petroleum hydrocarbon contents reduced by 65% for TC, TD and 52% for TE. Total organic carbon increased from 7.6±0.7 to 8.5±0.5%%, reduced from 4.0±0.1% to 3.7±0.3% and from 4.1±0.1% to 2.2±1.0% TC, TD and TE respectively. Total nitrogen increased from 0.66±0.1 to 0.69±0.0% for TC, remained nearly the same for TD and reduced from 0.4±0.0 to 0.2±0.0% for TE while average phosphorus increased from 0.4±0.0 to 23.0±4.2 mg/kg, 0.3±0.0 to 1.8±0.4 mg/kg and from 0.2±1.0 mg/kg to 52.6±4.6 mg/kg for TC, TD and TE respectively. Conclusively, combined amendment with oil palm bunch ash and sawdust did not induce synergism in soil total petroleum hydrocarbon content reduction. © JASEM